Harga diri dan citra tubuh sebagai prediktor kecenderungan body dysmorphic disorder pada remaja perempuan - Prastuti, Endang; Mulyani, Hanifah Tri (Persona:Jurnal Psikologi Indonesia, 2020)
Abstract Adolescent girls in their development period are more vulnerable to have mental health problems, one of which is Body Dysmorphic Disorder. This is related to the condition of physical change experienced by adolescent girls. This study aims to determine how much self-esteem and body image can predict the tendency of Body Dysmorphic Disorder in adolescent girls, both partially and simultaneously. This study uses a quantitative approach to the type of correlational research. The sampling techniques used in this study were proportional stratified random sampling with the research subjects were 152 adolescent girls at SMAN 1 Purwosari. This study uses research instruments in the form of self-esteem scales, body image scales, and body dysmorphic disorder tendency scales, compiled by researchers. The results of statistical analysis conducted using multiple regression test showed that self-esteem and body image can predict the tendency of body dysmorphic disorder significantly and negatively. These results indicated that self-esteem and body image are important factors against the tendency of body dysmorphic disorder. Therefore, it is necessary for adolescent girls to understand the importance of self-esteem and the development of positive body image at the age of adolescence.Keywords: adolescent girls; body image; self esteem; tendencies to body dysmorphic disorder AbstrakRemaja perempuan dalam masa perkembangannya rentan mengalami berbagai masalah kesehatan mental, salah satunya Body Dysmorphic Disorder. Hal ini berkaitan dengan perubahan kondisi fisik yang dialami oleh remaja perempuan. Tujuan penelitian ini yaitu untuk mengetahui sejauh mana harga diri dan body image dapat menjadi prediktor dari kecenderungan body dysmorphic disorder pada remaja perempuan baik secara parsial maupun stimultan. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian korelasional. Teknik sampling yang digunakan dalam penelitian ini yaitu proportional stratified random sampling dengan subjek penelitian berjumlah 152 remaja perempuan di SMAN 1 Purwosari. Instrumen penelitian ini menggunakan skala harga diri, skala citra tubuh dan skala kecenderungan body dysmorphic disorder yang disusun oleh peneliti. Hasil analisis statistik menggunakan uji regresi ganda menunjukkan bahwa harga diri dan citra tubuh menjadi prediktor yang signifikan terhadap kecenderungan body dysmorphic disorder dengan arah pengaruh yang negatif. Hasil ini mengindikasikan bahwa harga diri dan citra tubuh menjadi faktor penting yang berperan sebagai prediktor kecenderungan body dysmorphic disorder. Implikasi temuan: perlu bagi remaja perempuan dalam memahami pentingnya penghargaan diri dan pengembangan citra tubuh yang positif pada usia remaja.Kata Kunci: citra tubuh; harga diri; kecenderungan body dysmorphic disorder; remaja perempuan